Analisis Kesalahan Siswa Kelas IX SMP Negeri 3 Tondano Dalam Menyelesaikan Soal Cerita Pokok Bahasan Kekongruenan dan Kesebangunan - Arbi Maarial; Cory Pitoy; Jorry Ferry Monoarfa (Departement of Mathematics Education, 2024)
The study aims to analyze the mistakes of students in solving stories related to the material of congruence and construction in the 9th grade of the 3rd Tondano State High School. This research is a qualitative descriptive research with research subjects being 32 students and selected 6 students as samples of interviews. Data is collected through observations, written tests, and interviews. Data analysis is done through data summaries, data presentation, and interpretation. There are three types of errors observed, i.e. I misunderstood the problem, II mismade the mathematical model, III misled the algebraic operation. The results of the study showed that Type II error was the most common error, with 32 students making this error on issue 2. The error percentage reached 100%, suggesting that this error occurred in all students tested. Type III error, also occurred at a significant number, namely 27 students on issue 3, with a rate of error of 84%. The combination of Type II and III errors on issue 4, which combines both types of errors, shows that the majority of students (27 students percent 84%) make type II mistakes, while the number of students who make type III mistakes (26 students percent 81%) is also quite high. It suggests that the combination of both types of errors is still a challenge in understanding and applying mathematical concepts. The conclusion is that students have difficulties mainly in creating mathematical models (type II errors), performing algebraic operations (typ III errors) and a combination of both types of errors in solving mathematics issues. By knowing what kinds of common mistakes occur, teachers can focus on areas that require more attention to the problems that occur so that the learning process can be optimized and students are able to master the mathematical concepts.